2017
DOI: 10.1016/j.sleep.2017.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between sleep and anxiety during pregnancy, and the moderating effect of resilience, using parallel process latent growth curve models

Abstract: The results suggested that pregnant women reporting anxiety problems should also be screened for sleeping problems, and vice versa, because women who experienced one of these pregnancy-related problems were also at risk of experiencing or developing the other problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
(32 reference statements)
1
18
1
1
Order By: Relevance
“…Being resilient during the perinatal period has many positive consequences such as personal growth, family balance, well-being, adaptation, or adjustment (Nichols and Roux, 2004;Callahan and Borja, 2008;Mautner et al, 2013;Elmir, 2014;Takegata et al, 2014;Irwin et al, 2016;Mizukoshi et al, 2016;van der Zwan et al, 2017). Perinatal resilience can play a major role in buffering against antepartum and postpartum depression and anxiety (Takegata et al, 2014;Sexton et al, 2015;Hain et al, 2016;Irwin et al, 2016) and has a positive influence on the quality of life (Mautner et al, 2013;van der Zwan et al, 2017). When perinatal resiliency attributes are absent, some negative consequences may occur such as perinatal anxiety or postpartum depression.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Being resilient during the perinatal period has many positive consequences such as personal growth, family balance, well-being, adaptation, or adjustment (Nichols and Roux, 2004;Callahan and Borja, 2008;Mautner et al, 2013;Elmir, 2014;Takegata et al, 2014;Irwin et al, 2016;Mizukoshi et al, 2016;van der Zwan et al, 2017). Perinatal resilience can play a major role in buffering against antepartum and postpartum depression and anxiety (Takegata et al, 2014;Sexton et al, 2015;Hain et al, 2016;Irwin et al, 2016) and has a positive influence on the quality of life (Mautner et al, 2013;van der Zwan et al, 2017). When perinatal resiliency attributes are absent, some negative consequences may occur such as perinatal anxiety or postpartum depression.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the concept of psychological resilience stems from the early psychiatric literature that examined children who appeared to be invulnerable to adverse life situations (Hunter, 2001;Tusaie-Mumford, 2001;Henry, 2002;Pilowsky et al, 2004). A study of Werner and Smith (1982) with 698 individuals, showed that of the children that grew up in poverty or other adverse conditions (e.g., parental divorce, alcoholism, or mental illness), approximately two-thirds of these children developed serious problems as adults.…”
Section: Identifying Uses Of the Conceptmentioning
confidence: 99%
See 3 more Smart Citations